Serendipity [videorecording (DVD)] - Chelsom, Peter, 1956-; Cusack, John, 1966-; Beckinsale, Kate; Shannon, Molly, 1964- (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2002)
Is there really such a thing as a benevolent destiny that will eventually reunite true soul mates separated by time and distance? It begins at Christmastime in a New York department store, where two people meet by chance -- while shopping for their "significant others" -- and are immediately attracted to each other. After spending a romantic evening together, they reluctantly part, secretly hoping that fate will reunite them some day.